EXPLORATION OF TAX COMPLIANCE DETERMINATION ON MICRO, SMALL AND MEDIUM ENTERPRISE - Agus Supriyono; Intiyas Utami; Ali Muktiyanto (Jurnal Akuntansi, 2021)
The background of this research is the contribution of tax revenue from the Small Micro and Medium Enterprises (MSMEs) sector which is still less than the national tax revenue although the amount of tax revenue from the UMKM sector continues to grow. This condition occurs after the government issued special tax rates for MSMEs through Government Regulation Number 46 of 2013 and most recently amended through Government Regulation Number 23 of 2018. The sources of this research are the MSMEs taxpayers in Tegal City, Tegal Regency, and Brebes Regency which consist of industry players, store building owners, food stall owners, transportation service actors, workshop owners, gold shop owners, and fishing tool shop owners. This research was made using a qualitative research design with a qualitative descriptive approach. The conclusion obtained from this research is that MSMEs tax compliance is influenced by the determinants of the modernization of the taxation system (e-System), the financial condition of taxpayers, financial records, service from tax officers, the level of tax awareness, transparency of information on the use of tax results, the level of understanding of taxpayers. Taxes, tax systems, tax sanctions, and annual tax return forms. The theoretical benefit of this research is that it can be used as a reference in the development of further research, increasing knowledge about the theory related to tax compliance and the factors that affect the level of compliance of MSMEs in carrying out their tax obligations. The practical benefit of this research is that it can provide input for the Government to design regulations that can be understood by all levels of society and supported by simple and applicable instruments. As well as being able to contribute to MSMEs so that they can participate in national development through fulfilling honest and open tax obligations